Examining the Relationships among Cognitive Ability, Domain-Specific Self-Concept, and Behavioral Self-Esteem of Gifted Children Aged 5–6 Years: A Cross-Sectional Study - Dimitrios Papadopoulos (Behavioral Sciences, 2021)
Although childhood is a critical period of development during which all children begin a lifelong process of self-discovery that shapes their identities, few studies have focused on the self-concept and self-esteem of young, gifted children. This study recruited 108 gifted children aged 5–6 years from Greece and their preschool teachers to explore the relationships among cognitive ability, domain-specific self-concepts, and global self-esteem. The Pictorial Scale for Perceived Competence and Social Acceptance was used to assess the domain-specific self-concepts of the participants, whereas behavioral manifestations of self-esteem were rated by the children’s teachers using the Behavioral Academic Self-Esteem Scale. There were positive correlations among IQ, perceived scholastic competence, and global self-esteem. Hierarchical regression analysis indicated that significant predictors of global self-esteem were male gender, higher IQ, perceived scholastic competence, and perceived maternal acceptance. Additionally, there were gender differences in global self-esteem and perceived physical competence in favor of boys, whereas perceived maternal acceptance favored girls. This article discusses the need for practitioners working with gifted children to enact a comprehensive social–emotional learning curriculum in schools that promotes academic as well as personal and character strengths. Finally, the limitations of the study and suggestions for future research are also presented.